2006
DOI: 10.1111/j.1743-6109.2006.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal nicotine patch enhances type I collagen synthesis in abstinent smokers

Abstract: Cigarette smokers deposit less collagen, expressed as hydroxyproline, in granulation tissue than nonsmokers. We studied the effect of abstinence from smoking and transdermal nicotine patches on deposition of hydroxyproline, proline, type I procollagen, and total proteins. Fifty-four healthy smokers were studied during 10 days of smoking and again from days 10 to 20 following smoking cessation. After the first 10 days of abstinence they were randomized to double-blind treatment with transdermal nicotine patches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
5
23
0
Order By: Relevance
“…This view is supported by the fact that the blood levels achieved by nicotine infusion were similar to the levels previously achieved by nicotine-replacement drugs [34], which have been shown not to affect wound healing unless administered in toxic doses [35,36]. In fact, recent animal studies have found that nicotine appears to stimulate wound healing and angiogenesis [37,38], and human studies of abstinent smokers using transdermal nicotine patch have found normalized digital blood flow, enhanced collagen synthesis, and a nonexistent effect on incisional wound complications [17][18][19].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This view is supported by the fact that the blood levels achieved by nicotine infusion were similar to the levels previously achieved by nicotine-replacement drugs [34], which have been shown not to affect wound healing unless administered in toxic doses [35,36]. In fact, recent animal studies have found that nicotine appears to stimulate wound healing and angiogenesis [37,38], and human studies of abstinent smokers using transdermal nicotine patch have found normalized digital blood flow, enhanced collagen synthesis, and a nonexistent effect on incisional wound complications [17][18][19].…”
Section: Discussionsupporting
confidence: 67%
“…A more recent study, however, has shown that the digital perfusion normalizes within 1 week after transdermal nicotine patch-assisted smoking cessation [17], and our group has disproved the hazardous effect of transdermal nicotine patch on wound healing and incisional wound infection in abstinent smokers [18,19].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, use of the nicotine patch or gum was not associated with decreased wound-tissue oxygen tension, thought to be a result of the reduced levels and rate of nicotine absorption in the patch or gum compared with smoked nicotine. 13,24 Two studies examined the ideal time for nicotine withdrawal to prevent necrosis in rats. Forrest et al 17 demonstrated that when nicotine injections were withheld for 2 weeks before surgery, flap survival was similar to controls.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…For heavy smokers who are unable to quit, it may be more practical to recommend cutting down to less than 1 PPD or switching to nicotine replacement therapy during this period, as either method had negligible risk in several studies. 13,24,62 Regarding surgical technique, we recommend limiting the use of grafts or flaps in heavy smokers, and undermining in the deep subcutaneous plane to preserve the blood supply from the subdermal plexus. For reconstruction requiring interpolated flaps, consider using the delay phenomenon to increase flap viability and maximize surgical outcomes in smokers.…”
Section: Conclusion and Recommendations For Dermatologic Surgerymentioning
confidence: 99%